Cell Expansion Patterns and Directionality of Wall Mechanical Properties in Nitella. - Richmond, Paul A. (1980)
As a means of assessing the extent to which deformation of isolated walls relates to in vivo cell expansion, the directionality of wall mechanical properties was examined in Nitella. Measurements were made of plastic and elastic deformation and creep under both uniaxial and multiaxial stress conditions. Walls of different structural characteristics were obtained from control, isopropyl N-phenylcarbamate (IPC)-treated and IPC recovery cells. Although microfibrils in the inner portion of the wall were transverse for control and recovery cells but random for IPC cells, all walls had similar over-all microfibrillar orientations. Consequently, differences in wall mechanical properties should reflect structural differences in the inner wall. It is the action of the prevailing stress pattern on the inner, not overall, wall microfibrillar organization which dictates the directionality of growth in Nitella. The results indicate that the directional character of expansion is preserved to a large extent in the mechanical properties of isolated walls, and that most, but not all, of the deformation is determined by the inner wall. In addition, directional differences in the threshold for acid-induced extension varied in accord with the pattern of inner wall microfibrils.